Higher education and fertility: Evidence from a natural experiment in Ethiopia - Miron Tequame; Nyasha Tirivayi (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
This paper studies the effect of womens higher education on fertility outcomes in Ethiopia. We exploit an abrupt increase in the supply of tertiary education induced by a liberalisation policy. Using an age discontinuity in the exposure to higher education reform, we find that education lowers fertility by 8 and increases the likelihood of never giving birth by 25. We explore the role of potential underlying mechanisms and find that this negative effect on fertility is channelled through positive assortative mating and the postponement of marriage and motherhood.
Keywords: O12; I23; I25; I38; J12; J13; 330; Fertility; Higher Education; Assortative Matching; Marriage; Policy Evaluation